(untitled) (Colombia Medica, 2006)
The Allgrove syndrome (also known as Triple A syndromes), was described by Allgrove et al. in 1978 as a familiar clinical entity of unknown etiology whose characteristic features are adrenal insufficiency, achalasia and alacrima. The usual presentation is during the first 10 years of life with dysphagia or severe adrenal insufficiency, few new cases have been discovered in adults, whose autonomic symptoms and neurological manifestations such as mental retardation, hyperreflexia, nasal speech, anisocoria, ataxia, postural hypotension and sexual dysfunction are predominant. At the Pediatric Endocrinology Service of Hospital Universitario San Vicente de Paúl, Medellín, Colombia, 5 patients have been identified with the clinical features of Allgrove syndrome. All patients have showed both alacrima and adrenal insufficiency. Achalasia has not been diagnosed in one patient, whose symptomatology is highly suggestive to the syndrome. Mental retardation is the most frequent neurological alteration seen. The mean age of presentation for alacrima was 3.8 years, for adrenal insufficiency was 4.7 years and for achalasia was 7.2 years. An interesting finding and occasionally reported is the presence of hypothyroidism, which is subclinic in three patients, transient hypothyroidism in one patient and clinical hypothyroidism in the other one.